2021
DOI: 10.2298/tsci190418416e
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic steady motion of Casson fluid with heat and mass transfer through porous medium past a shrinking surface

Abstract: The motion of non-Newtonian fluid with heat and mass transfer through porous medium past a shrinking plate is discussed. The fluid obeys Casion model, heat generation, viscous dissipation, thermal diffusion and chemical reaction are taken in our considered. The motion is modulated mathematically by a system of non liner partial differential equations which describe the continuity, momentum, heat and mass equations. These system of non linear equations are transformed into ordinary differential equations by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The main aim of the present study is to minify entropy generation to obtain better results by restricting physical parameters of the problem. The dimensionless form of entropy generation can be exhibited mathematically as follows [3]:…”
Section: Entropy Generation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The main aim of the present study is to minify entropy generation to obtain better results by restricting physical parameters of the problem. The dimensionless form of entropy generation can be exhibited mathematically as follows [3]:…”
Section: Entropy Generation Analysismentioning
confidence: 99%
“…The effect of micromagnetorotation (MMR) of a Hartmann micropolar flow on the heat transfer has been studied by Aslani and Sarris [2]. Eldabe et al [3] studied the motion of non-Newtonian fluid with mass and heat transfer a shrinking plate through porous medium. The importance of suction/injection for gravity modulation mixed convection is investigated due to an inclined sheet in micropolar fluid flow in the presence of thermal radiation and magnetic field by Ali et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…But these figures also are excluded. Figure (16), illustrates the effect of the microorganisms concentration parameter on the concentration of microorganisms , it is found that the concentration of microorganisms increases with an increase in the microorganisms concentration parameter in the interval [0, 1.2), while it decreases with an increase in the microorganisms concentration parameter in the interval (1.2, 5]. Also, the concentration of microorganisms increases with an increase in the the velocity ratio B in the interval [0, 1.8), while it decreases with an increase in the velocity ratio B in the interval (1.8, 5].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The study of non-Newtonian fluids has attracted attention in recent years because of the use of many applications in different fields such as industry and engineering. The different types of non-Newtonian fluids are explained by many researchers [10]- [16]. Bhatti et al [17] invitegated the flow of Jeffrey fluid with small suspended particles through tapered duct with compliant walls in the presence of magnetic field, the fluid is electrically conducting, incompressible, irrotational with constant density.…”
Section: Introductionmentioning
confidence: 99%
“…2-D mixed convection with heat transfer effect and concentration flow through a stretched layer was expended by Zeeshan et al [27]. Pal et al [28] studied the heat features with the non-Darcy flow in the existence of ohmic distraction, and El-Dabe et al [29] analyzed the non-Newtonian case and expanded the research of Pal and Mondal [28] for the shrinking surface.…”
Section: Introductionmentioning
confidence: 99%